Bioethanol Manufacturing from α-Cellulose Waste of Empty Palm Oil Frugs (Elaeis guineensis jack) with Hydrolysis Concetration Variations HCl and Cellulase Enzyme - Indra Masmur; Herliana Herliana; Bramwell Sitompul; Elvri Melliaty Sitinjak (Indonesian Journal of Chemical Science and Technology (IJCST), 2022)
This study uses raw materials containing lignocellulose, namely empty fruit bunches of oil palm. Oil palm empty fruit bunches were isolated to produce cellulose, hydrolyzed into simple sugars, fermented, and distilled. From the isolation of cellulose obtained α-cellulose of 19.9612 grams (26.6149%). Then it was hydrolyzed using HCl with a concentration variation of 15%; 20%; 25%; 30%; and enzymatically hydrolyzed using cellulase to produce simple sugars which were tested qualitatively with Benedict's reagent and Tollens reagent, then quantitatively tested by the Luff Schroll method. The higher the concentration of acid used, the higher the sugar will be. The best bioethanol obtained from acid hydrolysis is using 30% HCl with ethanol content of 6.54% and enzymatic 7.32%.